2023
DOI: 10.1039/d2bm01950g
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic interfacial crosslinking of TiO2-based nanocomposite hydrogels through thiol–norbornene reactions for sonodynamic antibacterial treatment

Abstract: Nanocomposite (NC) hydrogels used for sonodynamic therapy (SDT) face the challenges of lacking interfacial interactions between the polymers and nanomaterials as well as presenting uneven dispersion of nanomaterials in the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…On the other hand, ultrasonic stimulation can also stimulate inorganic materials to produce ROS for tissue regeneration. Yang et al 207 fabricated a therapeutic hydrogel with acoustic-dynamic capabilities, incorporating antibacterial characteristics. This was achieved by employing mesoporous silica-coated titanium dioxide NPs (TiO 2 @MS-SH) as a crosslinking agent and ROS generator.…”
Section: Inorganic Fillers Building the Base For Smart Hydrogelsmentioning
confidence: 99%
“…On the other hand, ultrasonic stimulation can also stimulate inorganic materials to produce ROS for tissue regeneration. Yang et al 207 fabricated a therapeutic hydrogel with acoustic-dynamic capabilities, incorporating antibacterial characteristics. This was achieved by employing mesoporous silica-coated titanium dioxide NPs (TiO 2 @MS-SH) as a crosslinking agent and ROS generator.…”
Section: Inorganic Fillers Building the Base For Smart Hydrogelsmentioning
confidence: 99%
“…The gamma radiation technique allowed for producing a stable and sterilized hydrogel template. Yang et al 52 discuss a novel method for creating nanocomposite hydrogels-based TiO 2 @MS-SH nanoparticles for sonodynamic therapy. The process involves the utilization of specialized nanoparticles, specifically titanium dioxide nanoparticles coated with mesoporous silica and functionalized with thiol groups.…”
Section: Nanocomposite Hydrogel Formulation and Designmentioning
confidence: 99%
“…In a study by Yang et al, they reported ultrasonic-responsive antibacterial mesoporous silica-based nanomaterials. They utilized mesoporous silica-coated titanium dioxide nanoparticles with thiolated surface functionalization (TiO 2 @MS-SH) as crosslinkers [ 115 ]. The nanoparticles reacted with norbornene-functionalized dextran (Nor-Dex) through ultrasound-triggered thiol-norbornene reactions, leading to the formation of TiO 2 @MS-SH/Nor-Dex nanocomposite hydrogels.…”
Section: Stimuli-responsive Antibacterial Nanomaterialsmentioning
confidence: 99%